Penerapan Aplikasi Pendukung Touring pada Komunitas Motor Berbasis Android - M Khairul Anam; Reksi Anwar (Jurnal Pendidikan Informatika (EDUMATIC), 2020)
Google map is a road guide application to facilitate people getting some alternative routes to get a certain location, unfortunately. Google has no features to support touring facilities. Touring usually carried out by motor or car communities and followed by more than one vehicle. While touring sometimes, the members left behind or lost without knowing by the Road Captain. This is one of the obstacles to get the destination on time, because of the road captain is late knowing the members who lost and left behind. The purpose of this research is to create a touring application, which has a notification feature. The notification will light up when a member moves away from the Road Captain with a certain calculation radius. Members who lost can identify quickly so that the touring activities can run smoothly. This application has been tested by one of the motorcycle communities in Pekanbaru. After carrying out a trial, it proved that this application is very helpful for their touring trips. This application can run on Android operating system 5 and above. Therefore, it can be concluded that this touring application can be used, and it is feasible for traveling trips to various regions by motorcycle or car community